Volleying plasma membrane proteins from birth to death: Role of J-domain proteins - Sagarika, Preeti; Yadav, Kirpa; Sahi, Chandan (Frontiers in Molecular Biosciences, 2022)
The function, stability, and turnover of plasma membrane (PM) proteins are crucial for cellular homeostasis. Compared to soluble proteins, quality control of plasma membrane proteins is extremely challenging. Failure to meet the high quality control standards is detrimental to cellular and organismal health. J-domain proteins (JDPs) are among the most diverse group of chaperones that collaborate with other chaperones and protein degradation machinery to oversee cellular protein quality control (PQC). Although fragmented, the available literature from different models, including yeast, mammals, and plants, suggests that JDPs assist PM proteins with their synthesis, folding, and trafficking to their destination as well as their degradation, either through endocytic or proteasomal degradation pathways. Moreover, some JDPs interact directly with the membrane to regulate the stability and/or functionality of proteins at the PM. The deconvoluted picture emerging is that PM proteins are relayed from one JDP to another throughout their life cycle, further underscoring the versatility of the Hsp70:JDP machinery in the cell.